2009
DOI: 10.1152/advan.00040.2009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Virtual Physiology of Exercise Laboratory program

Abstract: The Virtual Physiology of Exercise Laboratory (VPEL) program was created to simulate the test design, data collection, and analysis phases of selected exercise physiology laboratories. The VPEL program consists of four modules: 1) cardiovascular, 2) maximal O(2) consumption (Vo(2max)), 3) lactate and ventilatory thresholds, and 4) respiratory exchange ratio. The purpose of this investigation was to compare student learning from the VPEL program with that from traditional "hands-on" exercise physiology laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Nevertheless, a number of studies in various disciplines have reported results suggesting that a virtual or at-home laboratory can be comparable to the traditional laboratory in terms of learning outcomes (Casanova et al 2006;Dobson 2009;Feig 2010). Brinson (2015) completed a comprehensive review of empirical studies comparing the effectiveness of traditional and nontraditional (online) labs, using a model he developed for categorizing learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a number of studies in various disciplines have reported results suggesting that a virtual or at-home laboratory can be comparable to the traditional laboratory in terms of learning outcomes (Casanova et al 2006;Dobson 2009;Feig 2010). Brinson (2015) completed a comprehensive review of empirical studies comparing the effectiveness of traditional and nontraditional (online) labs, using a model he developed for categorizing learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies suggest that virtual labs can combat budget cuts due to the reduced spending on staff and equipment [6], [7], [10]. This is evident for the Ryerson University virtual labs since the gain in funding is the net amount after accounting for the reduced money being spent on laboratory space and personnel.…”
Section: Resultsmentioning
confidence: 99%
“…One such instance is the use of a virtual physiology of exercise laboratory program at the University of Florida (Department of Applied Physiology ad Kinesiology). Students at this institute had simulated test designs and data collection of various physiological modules as opposed to traditional hands-on lab activities [6]. The merit of this approach to virtual labs is that well designed software can be easily distributed to a large number of students while completely bypassing the need for purchasing or maintaining specialized equipment [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, no studies have been done to investigate the impact of V-Labs, in general, or inquiry-based V-Labs, in specific, on secondary students. Very few studies have been conducted on university students majoring in biotechnology (e.g., Dalgarno, Bishop, Adlong, & Bedgood, 2009; Dobson, 2009). Since science at the secondary level becomes increasingly complex and abstract, it is important to study instructional approaches that would simplify its teaching.…”
Section: Biotechnology In Science Teachingmentioning
confidence: 99%